Strategi Pembelajaran Snowball Throwing untuk Meningkatkan Representasi Matematis pada Materi Diagram Batang Kelas IV - Inar, Iis; Irawati, Riana; Isrok’atun (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of the snowball throwing learning strategy in improving the mathematical representation of fourth-grade students on bar diagram material. The method used is a quasi-experimental design with a Nonequivalent Control Group Design. The study population was fourth-grade elementary school students in Conggeang District, with research samples from Cidempet Public Elementary School, Kawungluwuk Public Elementary School, and Narimbang 1 Public Elementary School. The experimental class used the snowball throwing strategy while the control class used conventional learning. The research instruments included essay test questions on mathematical representation, planning observation sheets, implementation observation sheets, and student activity observation sheets. The results showed that there was a higher increase in mathematical representation in students who learned with the snowball throwing strategy with a gain value of 0.71 (high category), compared to conventional learning which obtained a gain value of 0.50 (medium category). Thus, the snowball throwing strategy proved effective in improving students' mathematical representation. This strategy can be an alternative learning that is able to improve mathematical representation. Students are easier to express ideas in the form of pictures, symbols, and explanations.